KUALITAS PELAYANAN, HARGA DAN KUALITAS PRODUK IPENGARUHNYA TERHADAP KEPUTUSAN PEMBELIAN DI BEDAK ES TEH - Dharma Putra, Putu Riska; Trisnadewi, Ni Kadek Ayu (Komunitas Manajemen Kompetitif, 2024)
There will be a phenomenon related to a decline in sales in 2023. The decline in sales of contemporary tea drinks in Iced Tea Powder is predicted to continue if we do not take strategies to anticipate it. Therefore, management requires a serious understanding of the factors that influence sales volume growth to continue increasing it in order to maintain and increase consumer purchasing decisions. In connection with this problem, it is necessary to investigate further the factors that influence the decision to purchase Ice Tea Powder drinks, including service quality, price and product quality. This research aims to determine the influence of service quality, price and product quality on purchasing decisions at Bedak Iced Tea. The population in this study were consumers of Iced Tea Powder. The number of population members is unknown. The number of samples that will be used in this research is 75 respondents who are consumers of Iced Tea Powder. Data analysis techniques are techniques for processing data that is collected and then interpreting the results of the analysis which will be used to answer the problems that have been formulated. The data analysis method used to solve the problem in this research is multiple linear regression analysis which will be carried out using the SPSS (Statistics Program and Service Solution) program. Based on the results of the analysis and discussion, it is known that service quality has a positive effect on purchasing decisions. This means that the better the quality of service has an influence on the increase in purchasing decisions. Price has a positive effect on purchasing decisions. This means that the better the price, the higher the purchasing decision will be. Product quality has a positive effect on purchasing decisions. This means that the better the product quality, the higher the influence on purchasing decisions.